Management Information System Model For The Family Hope Program - Akbar, Rizky Fadila Muhammad; Khairullah, Khairullah; Ariannor, Wahyudi (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The data collection and management of PKH assistance experience various problems, such as lack of efficiency, inaccurate distribution times, lack of accountability, and difficulty in accessing information for the community. The proposed approach is to build a web-based and Android mobile information system using the DevOps development method. This system was tested using black box testing techniques. The research results show that the system developed successfully fulfills all the specified functional requirements. Using this system can facilitate PKH data management, speed up the decision-making process regarding aid distribution, and increase transparency and access to information for the community. This research recommends continuing development with further integration with related systems, the development of mobile applications for beneficiaries, and deployment in other regions.Keywords: Information System; Social Assistance; Efficiency; Effectiveness of Service QualityÂ AbstrakPendataan dan pengelolaan bantuan PKH mengalami berbagai masalah seperti kurangnya efisiensi, ketidaktepatan waktu penyaluran, kurangnya akuntabilitas, serta sulitnya akses informasi bagi masyarakat. Pendekatan yang diusulkan adalah membangun sistem informasi berbasis web dan mobile Android menggunakan metode pengembangan DevOps. Sistem ini diuji dengan menggunakan teknik pengujian blackbox. Hasil penelitian menunjukkan bahwa sistem yang dikembangkan berhasil memenuhi semua kebutuhan fungsional yang ditetapkan. Penggunaan sistem ini dapat memudahkan pengelolaan data PKH, mempercepat proses pengambilan keputusan terkait penyaluran bantuan, serta meningkatkan transparansi dan akses informasi bagi masyarakat. Penelitian ini merekomendasikan untuk melanjutkan pengembangan dengan integrasi lebih lanjut dengan sistem terkait, pengembangan aplikasi mobile untuk penerima manfaat, dan penyebaran di wilayah lain.Â